The Role of Contemporary CO2 Sublimation as a Geomorphic Agent on Mars - MC KEOWN, LAUREN EVE (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2019)
The Martian surface is geomorphologically active, with a variety of mass?wasting, erosional and depositional features that form and change in the current climate. Many of these features have analogues on Earth (e.g. Alcove-Channel-Apron (ACA) gullies, dust devil tracks) and therefore there is a long history of observational studies of the processes which may have shaped them. Conversely, some features differ from Terrestrial scales and morphologies and others are completely unlike any seen on Earth. These include linear dune gullies, the dendritic araneiform terrain and associated fans and spots of the southern high latitudes and the faint sand furrows etched across polar dunes. All of these features have been attributed to seasonal carbon dioxide sublimation. While elegant numerical and conceptual models have attempted to elucidate their specific formation mechanisms, the dynamics of CO2 sublimation and its interaction with sediment is still weakly understood. This thesis chronicles a four year long campaign to provide for the first time, quantitative empirical data on CO2 sublimation and its interaction with granular material. This work documents and quantifies sediment mobilisation styles and morphological change when a granular bed is subject to CO2 sublimation and sand furrows, pits and araneiforms develop. A survey of high resolution images and topographic models of morphologically analogous features on Mars is presented and laboratory results are synthesised in the context of the Martian scale. This work subsumes a rigorous tool which can be used by future studies to advance our understanding of the Martian surface and the processes which shape it today and concludes that CO2 sublimation is an efficient and dynamic agent of change to the contemporary Martian surface over short timescales.
APPROVED
Keywords: Mars; Geomorphology; Carbon Dioxide Ice; Sublimation; Planetary Science; Polar Processes